2011
DOI: 10.7751/telopea20116015
|View full text |Cite
|
Sign up to set email alerts
|

Hybridisation in a tropical seagrass genus, Halodule (Cymodoceaceae), inferred from plastid and nuclear DNA phylogenies

Abstract: The tropical seagrass genus, Halodule, is distributed in warm to tropical areas throughout the world. We performed separate molecular phylogenetic analyses of Halodule based on both plastid and nuclear DNA sequences, followed by haplotype analysis, focusing on plants in the western Pacific area. One western tropical Atlantic species, H. wrightii s.l., and two western Pacific species, H. pinifolia and H. uninervis, were recognised and characterised by leaf morphology. Because samples from the western tropical A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Halodule pinifolia and H. uninervis were resolved as distinct species. Taxonomic segregation of Halodule pinifolia from H. uninervis is not clearly resolved based on trnL (Waycott et al, 2006), single rbcL (Ito & Takahata, 2011) and rbcL/matK barcode (Lucas et al, 2012). In addition, a hybrid in the genus Halodule based on phyB analyses was detected (Ito & Takahata, 2011).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Halodule pinifolia and H. uninervis were resolved as distinct species. Taxonomic segregation of Halodule pinifolia from H. uninervis is not clearly resolved based on trnL (Waycott et al, 2006), single rbcL (Ito & Takahata, 2011) and rbcL/matK barcode (Lucas et al, 2012). In addition, a hybrid in the genus Halodule based on phyB analyses was detected (Ito & Takahata, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…Taxonomic segregation of Halodule pinifolia from H. uninervis is not clearly resolved based on trnL (Waycott et al, 2006), single rbcL (Ito & Takahata, 2011) and rbcL/matK barcode (Lucas et al, 2012). In addition, a hybrid in the genus Halodule based on phyB analyses was detected (Ito & Takahata, 2011). However, the recent analysis of two plastid (matK, rbcL) and four mitochondrial genes (atp1, ccmB, cob, nad5) indicated that H. uninervis and H. pinifolia are distinct species (Petersen et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Either of these reasons may cause incongruence between ITS and plastid phylogenies. Among marine angiosperms, natural hybridization has been observed in only four genera (Halodule, Ruppia, Posidonia, and Zostera) (Ito & Tanaka, 2011;Coyer et al, 2008;Martínez-Garrido et al, 2016;Sinclair, Cambridge & Kendrick, 2019). Ito & Tanaka (2011) found sympatric Halodule uninervis and H. pinifolia hybridizing in the waters of Okinawa by reconstructing their phylogenetic relationship with rbcL and psbA-trnH loci.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is known to facilitate their resistance to global change in different ecological niches [47][48][49][50][51]. Probably, the origins of morphotype for a species, is intraspecific polymorphism, speciation in progress, incomplete derivation sorting or hybridization through introgression [52][53] reported for the Cymodoceaceae family [54].…”
Section: Discussionmentioning
confidence: 99%